A historical reflection from a prison perspective (Estudios de Historia de España, 2017)
Prisons are an inevitable part of the model of society that wants to do it. This paper is about the Spanish prisons, their different models and reflects changes in Spanish society with the arrival of the Spanish Constitution of 1978.
Keywords: History of Spanish prisons; Prison models; Spanish military prison system; Transformation of the army